P67 Development of a data quality framework for health and social care – a strategic approach to assess and improve the quality of health data and information in ireland. (3rd September 2019) - Healy, A; Duggan, C; Foley, B; Flynn, R; Huss, T
Abstract : Background: A considerable amount of data is collected on a regular basis about health and social care services in Ireland. We rely on this for the planning and delivery of safe and efficient services and to inform future policy and service planning. Therefore, it is vital that there is confidence and trust in the quality of this data in order to support the provision of safe and efficient care to patients and service users. The aim of this research was to develop guidance on the development of a data quality framework for health and social care organisations in Ireland, to enable them to systematically assess, monitor, evaluate and improve the quality of their data and information. Methods: This research involved four key stages; an international review of evidence to compare and contrast international approaches as well as the key components of a data quality framework, the establishment of an Expert Working Group to provide advice and knowledge, interviews and consultation with national and international experts, and finally, the conduct of a targeted consultation with a wide range of stakeholders including national evidence and policy makers, representatives from national data collections, service providers and academia. The findings were collated and assessed thematically in order to inform the finalised guidance. Results: Guidance on a data quality framework for health and social care organisations in Ireland was developed. The components of the framework include: a data quality strategy which outlines key components including audit, governance and training; a data quality assessment tool which provides a detailed set of criteria organisations can use to comprehensively assess its data sources across all five dimensions of quality; reporting on data quality using key performance indicators and data quality statements, and a data quality improvement cycle detailing the continuous approach organisations can undertake to improve the quality of their data and information. Conclusion: The guidance, which is the first of its kind in Ireland, provides tools to support health and social care organisations in ensuring that their data is 'fit for purpose'. By applying this guidance, it is possible for organisations to establish a baseline for data quality and identify areas for improvement. Where organisations adopt a systematic approach to assessing, improving and maintaining the quality of their data, sector-wide improvements in the quality of data can be observed and stakeholders can be assured that the data they use to support decision making is of high quality.